Employee Motivation Strategies and Performance of the Commercial State Corporations in Kenya - Kimeu, Hillary; Wamwayi, Scholastica (Human Resource and Leadership Journal, 2026)
Purpose: The general objective of this study is to examine the influence of employee motivation strategies on performance of the commercial state corporations in Kenya. Specifically, the study sought to assess the influence of work-life balance policies on performance of the commercial state corporations in Kenya and to establish the influence of employee reward system on performance of the commercial state corporations in Kenya. This study was guided by Conservation of Resources (COR) Theory and Equity Theory. Methodology: This study used a cross-sectional survey design. The study targeted a total of 184 respondents comprising of employees working the human resource department in commercial state corporations in Kenya. The study adopted Yamane (1957) to determine the appropriate sample size. Hence, the sample size of the study was 126 respondents. In this study, primary data was collected using a semi structured questionnaire. This study used closed-ended questions to collect the data. The researcher collected questionnaires, code them, and enter them into the Software Package for Social Sciences (SPSS version 26) for analysis. The descriptive statistical techniques of frequency, mean, and standard deviation was used to analyze the quantitative data acquired. Inferential statistics including regression and correlation analysis was used in the study. Pearson correlation coefficient was used for testing associations between the independent and the dependent variables. A multiple regression model was used to test the significance of the influence of the independent variables on the dependent variable. Findings: The study concludes that work-life balance policies have a positive and significant influence on performance of the commercial state corporations in Kenya. In addition, the study concludes that employee reward system has a positive and significant influence on performance of the commercial state corporations in Kenya. Unique Contribution to Theory, Policy and Practice: Based on the findings, the study recommends that the management of commercial state corporations in Kenya should strengthen and modernize their employee reward systems by adopting a performance-based approach that fairly links rewards to measurable individual and organizational outcomes.